DYNAMICS OF CONCENTRATION OF NEUROSPECIFIC PROTEINS IN THE BLOOD OF PREMATURE INFANTS WITH RESPIRATORY DISTRESS SYNDROME ON THE BACKGROUND OF COMPLEX THERAPY - Асадова С. І. (World of Medicine and Biology, 2015)
90 premature newborns with SDR have been examined. The children were admitted to the ICU for the first 24-72 hours of life. Depending on the gestational age newborns were divided into 3 groups: I group - 30 infants aged 28-30 weeks. of gestation; group II - 30 newborns at the age of 31-33 weeks. of gestation, and group III - 30 infants 34-36 weeks. of gestation. The level of NSE in the blood of newborns with RDS and CNS was higher than that of newborns with RDS without CNS by 25.6%, and GFK - 54,0% (p
Keywords: premature newborn; respiratory distress syndrome; surfactant